Thoughts on the theory and language of architecture : Lecture Series Part 1 Ar.Hijjas Kasturi - Abdullah, Azaiddy; Mohd Nawawi, Norwina; Jahn Kassim, Puteri Shireen (MPH Group Printing (M) Sdn.Bhd, 2009)
The book is the first installation of a lecture series presented by prominent architects of our time to the students and lecturers of Kulliyyah of Architecture and Environmental Design (KAED), International Islamic University Malaysia (IIUM). This first effort is a collaboration between KAED, IIUM and Hijjas Kasturi Associates Sdn. Materials for the book was taken from the lecture delivered by Ar.Hijjas Kasturi on 21st July 2006 and expanded by the editors.